Polymorphism-801G/A in the 3′-untranslated region of CXCL12 is not associated with preeclampsia in Chinese Han population. (2nd January 2017) - Xu, Jine; Chen, Kai; Li, Aiqin; Guo, Mingzhen; Wang, Jingli; Liu, Shiguo; Wang, Xiuhai
ABSTRACT: Objective : We investigated whether the CXCL12-801G/A polymorphism was associated with preeclampsia (PE) susceptibility in a Chinese Han population. Methods : We examined 912 PE women and 1025 controls for the CXCL12-801G/A polymorphism by polymerase chain reaction (PCR) and correlations with clinical characteristics were examined. Results : No significant differences in genotypic and allelic frequencies of CXCL12-G801A were found between cases and controls (genotype: χ 2 = 2.095, p = 0.351; allele: χ 2 = 1.713, p = 0.191). There were also no significant differences between early/late-onset or mild/severe PE and control groups. Conclusion : The results indicate that 801G/A in CXCL12 may not play a major role in pathogenesis of PE in a Chinese Han population.